Positive orientation, job satisfaction and psychological well-being of mental health practitioners in Malaysia. Issue 10 (26th November 2021) - Park, Miriam Sang-Ah; Goto, Nobuhiko; Kennedy, Alice; Raj, Sanjana; Dutson, Alexander; Park, Lauren; Sovet, Laurent
ABSTRACT: Mental health practitioners in many developing countries are faced with high job demands and a lack of institutional support. Given their high levels of work-related stress, it is important to identify mechanisms that help them to maintain psychological well-being and job satisfaction. Recent research has focused on the role that positive orientation (POS) may play in mediating the negative impact of stress on individual well-being. The present study investigated whether POS predicts mental health practitioners' perceived levels of stress, mental health and job satisfaction. If POS measures a person's tendency to take a positive attitude to life and their ability to cope with difficulties, a high POS could be linked to reduced levels of stress and increased levels of job satisfaction and well-being. This study examined associations between self-reported POS and psychological outcomes in a sample of 100 Malaysian mental health practitioners. The results showed that POS significantly predicted job satisfaction positively and mental health issues and perceived stress negatively, even when socio-demographic variables were controlled. Overall, we found a strong effect of POS on individual functioning across the sample of mental health practitioners. Our results have implications for improving practitioner wellbeing and job satisfaction.